IMPLEMENTASI STANDAR OPERASIONAL PROSEDUR BELLBOY PADA HOTEL ARYADUTA PEKANBARU - Robiyanto, Wiwit; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research aims to know how the implementation of S.O.P and the level of S.O.P implement by bellboy in Aryaduta Hotel Pekanbaru. This research is combine research between qualitative and quantitative. The population of this research is bellboy with number 6 persons, because of 6 bellboys will be analyzed in this research, the number of sample and respondent same as the population it self. Based on the research result that has been done by the writer, that Aryaduta Hotel’s management has said that implementation of S.O.P to bellboy is good enough and the level of S.O.P implement by bellboy is high.Keywords : Implementation, S.O.P, Bellboy, Management.